Izbrana novejša sodna praksa s področja plačila za delo - Kogej Dmitrovič, Biserka (Podjetje in delo, 2018)
The article presents the recent case law on remuneration for work. As it deals with disputes related to monetary claims, where a review is allowed for amounts of over 40,000 euros or below this sum if approved by the Supreme Court, case law of the latter is scarce, while the case law of higher courts is more extensive. The article examines decisions on question of maturity of salary and related payday and statute of limitation, decisions on salary offsets, amount of salary, agreed-upon salary and reduced salary, decisions on seniority-based pay increments, payment for holidays, payments in the event of unjustified absence from work and salary compensation, decisions related to various types of severance pays, and the decision of the higher court that changed the case law regarding decisions on payments of taxes and contributions from amounts awarded in labour disputes.
Keywords: dodatek za delovno dobo; nadomestilo plače; nadurno delo; odpravnina; plača; plačilo davkov in prispevkov; pobotanje plače; zapadlost plače